2008
DOI: 10.1128/iai.00614-08
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Pore Formation in Host Cell Membranes by ESX-1-Secreted ESAT-6 and Its Role in Mycobacterium marinum Escape from the Vacuole

Abstract: The ESX-1 secretion system plays a critical role in the virulence of M. tuberculosis and M. marinum, but the precise molecular and cellular mechanisms are not clearly defined. Virulent M. marinum is able to escape from the Mycobacterium-containing vacuole (MCV) into the host cell cytosol, polymerize actin, and spread from cell to cell. In this study, we have examined nine M. marinum ESX-1 mutants and the wild type by using fluorescence and electron microscopy detecting MCV membranes and actin polymerization. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
278
3
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(297 citation statements)
references
References 52 publications
13
278
3
3
Order By: Relevance
“…This strongly suggests that, regardless of the general similarity, the capacity to interact with the membranes in response to acidification is a hallmark of the ESAT-6 molecules associated with virulence. These findings are consistent with the membrane interaction studies of MmESAT-6, the reportedly membrane-interacting molecule from the pathogenic M. marinum (29). It would be interesting to look into the membrane interaction of other orthologous ESAT-6 proteins from both pathogenic and non-pathogenic species in relation to virulence.…”
Section: Discussionsupporting
confidence: 79%
“…This strongly suggests that, regardless of the general similarity, the capacity to interact with the membranes in response to acidification is a hallmark of the ESAT-6 molecules associated with virulence. These findings are consistent with the membrane interaction studies of MmESAT-6, the reportedly membrane-interacting molecule from the pathogenic M. marinum (29). It would be interesting to look into the membrane interaction of other orthologous ESAT-6 proteins from both pathogenic and non-pathogenic species in relation to virulence.…”
Section: Discussionsupporting
confidence: 79%
“…In this context, it is conceivable that the membrane-lysing or pore-forming activity exerted by ESAT-6 and/or other effector proteins of the ESX-1 system might be responsible for autophagy blockage during the early phases of infection while at later stages it allows the phagosome-to-cytosol translocation of Mtb. [40][41][42][43][44] Although in our experimental model it is not yet clear whether ESAT-6 modulates directly or indirectly the autophagic process, the results obtained so far strongly suggest that the functional interaction between ESAT-6 and the DC autophagosome/autolysosome machinery is crucial to influence the immune response against TB. 30 We also showed that rapamycin treatment restores a functional autophagic flux in Mtb-infected cells, as evaluated by the analysis of SQSTM1 levels and the colocalization of MAP1LC3 with the lysosomal markers LAMP1 and cathepsin B.…”
Section: Methodsmentioning
confidence: 87%
“…[40][41][42][43][44] However, since Mtb is still detected in vesicle structures 16 h after infection (ref. 44 and data not shown) when autophagy block is already fully visible, it is likely that the effect on autophagy was not exerted by cytosolic Mtb.…”
Section: Methodsmentioning
confidence: 99%
“…24 The ESAT-6 homolog from the ESX-1 system of M. marinum has also been implicated in disrupting host cell membranes and a genetic deletion of the ESAT-6 gene has been shown to eliminate the pore-forming ability of M. marinum. 8 To date…”
Section: Introductionmentioning
confidence: 99%
“…The canonical ESX complex, EsxAB, is encoded within the 9.5 kb region of difference 1 (RD1), which is the only common genetic deletion found in two attenuated mycobacterial vaccine strains [M. bovis bacillus Calmette-Guérin (BCG) and M. microti]. In vivo studies have determined that the RD1 locus is partially responsible for the virulence of M. tuberculosis, M. bovis, M. marinum, and M. microti [3][4][5][6][7][8] and complementation of BCG or the avirulent M. microti vaccine strain with RD1 increased the virulence of these strains. 6,9 Biochemical and bioinformatic analyses have determined that the RD1 locus encodes, in addition to EsxAB, the components of a protein secretion system, ESX-1, which is the prototypical member of the Type VII secretion system family (T7S system; reviewed in 10 ).…”
Section: Introductionmentioning
confidence: 99%